An Analysis Of Student’s Ability In Translating Thesis Abstract At Management Department In The Faculty Of Economy University Of Muhammadiyah Gresik - Nabila, Faricah (Journal of English Teaching, Literature, and Applied Linguistics, 2021)
Non-English Department students in the end of the study will need to create an abstract in English. As the students who do not learn English extensively, they have difficulties in translating abstract from Indonesia to English. Therefore, in their thesis abstracts are usually found some errors. This research has an objective to find the common errors committed by the students in translating thesis abstract. In this research, there were three main steps to find the result, first, the researcher gathered the documents and listed the errors committed by the students, then compared the errors to find the common one and the last, analyzed the students translation to find the average ability of the students in translating thesis abstract. The result showed the common errors in translation were caused by the difference of language pattern of source language and target language.